O statutach nowego rycerstwa .......... 121 - Wenta, Jarosław (Dzieje i kultura Cystersów w Polsce, 2025)
ON THE STATUTES OF THE NEW KNIGHTHOODThe Cluniac and Cistercian experiences with conversi groups appears to be absolutely essential to encourage reflection on the core documents of military orders, as it contributed to the amalgamation of the conversi formation (the conversi of the younger order in Cluny and Cistercians) and the fullness of order rights (the Cluniac conversi of the older order). These examples are of major significance due to the fact that the founders of the Knights Templar were – in lineal descent – the continuators of the group of knights who went through their religious adventure in Cîteaux and Cluny. This time they were to experience it in a new, both knightly and lay, form. With regard to vita religiosa, the writings include rules, consuetudines, and statutes – all laying down the normative structures of the religious community. Often drafted simultaneously in several medieval dialects of the vernacular, the different versions of particular statutes or rules are a unique phenomenon, thus, studying such texts, particularly editing them, requires more than just thorough philological preparation. The Teutonic Order provides an excellent example to observe the evolution of the rule of the Knights Templar and the manners of adapting it to the current needs of the autonomous houses (orders included) connected therewith. The first version of their original rule, i.e. the statutes of the order, in the form in which they are known today, originated between the years preceding 1244 – when the Teutonic Knights still unquestionably (the bull of Pope Innocent IV) observed the rule of the Knights Templar – and the day when the oldest German manuscript – which has been preserved until today – was drafted, i.e. St Remigius’s day (1 October) 1264. The common rules, purposes, and language can explain the taking over of the mission of the Livonian Brothers of the Sword or the order of brethren in Dobrzyń, established to conduct operations in Prussia. It is worth mentioning the direct source quoted by Klaus Schreiner, i.e. the commentary of Humbertus de Romanis from the mid-13th century. According to him, some monks did not have a written rule (nulla scripta). In their actions (in agendis suis), they relied on the origin of tradition, consuetudo, understanding, recognizing what seemed rational (rationabilis) to be the ratio. The establishment of consuetudines (consuetudinarium, ordo ordinarius, statute, in a narrower sense of the word) and Gewohnheiten resulted from the necessity of adapting original standards to the current situation of the community due to the natural passage of time. Since the time of Max Perlbach, no one has done any library search to expand the number of the linguistic versions known or the number of Latin or French manuscripts. An online portal containing descriptions of medieval German manuscripts, Handschriftencensus, is useful to become generally oriented in the resources. Descriptions of the manuscripts demonstrate that, by the late 13th century, many houses of the order had developed their own, local, redaction and linguistic traditions concerning the statutes. Apparently, the principle of the uniformity of liturgical books and basic documents did not exist, or was not adhered to properly, in the order. The Latin version is considered to be the closest to the original, order’s own, version of the statutes.